TABOO WORDS IN NICKI MINAJ SONGS - David BonarisTuaHutabarat and Lidiman Sahat Martua Sinaga (LINGUISTICA, 2016)
This study deals with types of taboo words in song lyrics of Nicki Minaj. The objectives of the study were to find out the types of taboo words used in song lyrics of Nicki Minaj, to determine the dominant type of taboo words used in song lyrics and to describe the uncategorized of types of taboo words used in song lyrics. This research was conducted by using descriptive qualitative research. The source of data was derived from song lyrics of Nicki Minaj. The data were taken from the taboo words used in those song lyrics. There were 130 words in the children’s song lyrics of nursery rhymes. The result of the analysis showed that all types of taboo words used in song lyrics of Nicki Minaj; Sexual Activity 55 words (42.31%) followed by numeral on parts of body on taboo words 48 words(36.92%), Religion or Believe 17 words (13.08%) and the last was lavatory or excretion 10 words (7.69%). The dominant types of taboo words used in song lyrics of Nicki Minaj are sexual activity with 55 words. It means that in the song lyrics contain or told about activity, action or event that are happened or doing which happen outside the human beings